Prescribing behavior of antidepressants for depressive disorders: A systematic review - Lam, Mary K.; Lam, Lawrence T.; Butler-Henderson, Kerryn; King, Jonathan; Clark, Tahnee; Slocombe, Peta; Dimarco, Katherine; Cockshaw, Wendell (Frontiers in Psychiatry, 2022)
Objective Guidelines for the prescription of antidepressants for Depressive Disorders (DD) have been in place for a long time. However, there is a lack of systematic information on the prescribing behaviour of antidepressants in clinical practice. This may suggest a lack of implementation of clinical guidelines by clinicians. Existing literature mainly focuses on specific issues or medications. To provide general information on the prescribing behaviour of antidepressants for depressive disorders, a systematic review of available studies since 2013 was conducted. Methods To ensure a structured and systematic approach for the literature search and subsequent review process, the PRISMA guidelines for systematic reviews were followed. Major medical and health and psychological databases were used for the literature search. These included Ebsco Host, OVID, PubMed, Science Direct, Scopus, and Web of Science. The online application ‘Covidence’ was employed to manage the titles collected and the full articles retrieved from the initial literature search. Upon finalising the list of selected studies, data extraction was then conducted using a build-in function of the Covidence platform with the required information pre-set on a template for data extraction. The extracted information was tabulated and summarised in a table. Results Forty-one studies were identified after an extensive search of the literature following the PRISMA guidelines. Of these, 37 quantitative studies providing useful information were systematically reviewed and information extracted. There was a high level of heterogeneity among these studies with different foci or characteristics. Most studies were conducted in or utilised data obtained from hospital and primary healthcare settings. SSRIs were the most commonly prescribed type of antidepressant in the past decade, particularly among younger patients. Among these studies, antidepressants were mainly prescribed by psychiatrists with some by other physicians and general practitioners. This might reflect differences in legislation regarding professional requirements for prescribers or clinical practices. Conclusions A few themes that would be considered important in terms of the effect of prescription behaviour on depression, specifically children/adolescents, special target populations, and off-label prescription. The results highlighted the need for more studies on a community-based approach and the role of GPs in the treatment of DD.